Institutional Investor Trading and Stock Price Informativeness: Empirical Evidence from the Vietnamese Stock Market - Nguyen Thu, Hang; Nguyen Thi Nhu , Hao; Nguyen Thi Thanh , Loan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This paper studies the effect of institutional investors' trading on the stock price informativeness of Vietnamese listed companies. Using two-stage regressions with 4,495 observations of 592 listed enterprises, we show that institutional investors transmit private information through their trading activities, thereby increasing the informativeness of the stock price. Notably, purchases by institutional investors contain positive signals, resulting in abnormal positive returns after the announcement day.
Keywords: Trading; Institutional investor; Stock price informativeness; Synchronicity; Stock price